Engineering an iron atom-cluster nanostructure towards efficient and durable electrocatalysis. Issue 15 (22nd March 2023) - Zheng, Feng-Yi; Li, Ruisong; Xi, Shibo; Ai, Fei; Wang, Jike
Abstract : The synergistic effect of Fe-based single-atoms and clusters in porous structures has significantly boosted the oxygen reduction reaction (ORR) activity, selectivity, and stability, as well as the application in energy storage. Abstract : Iron-based catalysts have demonstrated fascinating activities in the oxygen reduction reaction (ORR), especially due to the synergistic effect between atoms and clusters, but challenging for further improvement. Herein, a strategy is developed to optimize the catalyst with nitrogen-coordinated Fe single atoms (SAs) and closely surrounding Fe atomic clusters (ACs) towards efficient ORR. The FeSA /FeAC -NC 900 delivers excellent ORR activity with half-wave potential ( E 1/2 ) in both acidic (0.80 V) and alkaline (0.90 V) media, as well as superior stability. Theoretical calculations further reveal that the synergistic effects of Fe-based SAs and ACs along with porous structures can decrease the overall energy barrier in the ORR process. Besides, the FeSA /FeAC -NC 900-based zinc–air battery manifests a high peak power density (214.3 mW cm −2 ) and a high-specific capacity (773.6 mA h g −1 ). This work provides a new perspective to highly optimize the synergistic interaction of SAs and ACs for boosting activity and energy storage.